Differential expression of microRNAs in preneoplastic gastric mucosa - Link, Alexander; Schirrmeister, Wiebke; Langner, Cosima; Varbanova, Mariya; Bornschein, Jan; Wex, Thomas; Malfertheiner, Peter (Scientific Reports, 2015)
Gastric carcinogenesis is a multifactorial H.pylori-triggered dynamic process that goes through a cascade of preneoplastic conditions. The expression of miRNAs in the stomach with regard to preneoplastic precursor conditions and H.pylori infection has not been investigated systematically. In this prospective proof-of-principle study, we evaluated the miRNA expression in gastric antrum and corpus mucosa from patients with chronic non-atrophic gastritis (CNAG), atrophic gastritis (AG), and GC compared to controls. Gastric normal mucosa shows a unique expression pattern for miR-21, miR-155 and miR-223, which is specific for different regions. In correlation with progression of Correa's cascade and H.pylori infection, we observed a gradual increase in miR-155 and miR-223 both in corpus and antrum and miR-21 only in the antrum mucosa. Using miRNA expression we calculated a score that allowed us to discriminate patients with AG from subjects with normal mucosa with high diagnostic accuracy in testing and validation cohorts reproducibly. In summary, the expression pattern of miRNAs in the gastric mucosa is gradually increased with progression of Correa's cascade and H.pylori infection, suggesting miRNAs as potential biomarkers for preneoplastic precursor conditions. However, differences of miRNA expression between the gastric antrum and the corpus need to be considered in future studies.
CRIS-Team Scopus Importer:2025-10-13